SUMBER MANAJEMEN TENAGA MANUSIA DALAM MENGEMBANGKAN PENDIDIKAN BERKUALITAS DI UNIT PENDIDIKAN MUADALAH ULYA AL- AMIRIYAH BANYUWANGI - Munir, Mr. Luthfi; Wafa, Ali (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study reveals how continuous professional development, collective religious leadership, and organizational culture are the keys to educational quality at Mujadi Ulya Blokagung . The purpose of this study is to describe in depth the process and strategies for improving the quality of Islamic boarding school-based education by highlighting three main aspects: teacher professional development, leadership style, and organizational cultural values. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through participatory observation, in-depth interviews with leaders and teachers, and institutional documentation. The collected data were analyzed using thematic analysis techniques, which identified important patterns from experiences and practices in the field. The results of the study indicate that teacher development at Ulya Blokagung is contextual and transformative, with structured and spiritual training. Leadership that is carried out collectively and based on religious values creates strong organizational synergy. The deep-rooted Islamic boarding school culture becomes the spirit of education and an effective internal driver. Overall findings show that the integration of professional development, religious leadership, and Islamic boarding school culture has created a complete and sustainable educational ecosystem, and made Ulya Blokagung a model of a modern Islamic boarding school that remains based on traditional values.